Pohon regulačního kruhu PVE Merkersbach - Skoupý, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Diplomová práce řeší zejména problematiku silového působení servomotorů bez vyrovnání a s vyrovnáním sil na regulační kruh přečerpávací vodní elektrárny Markersbach (Německo). Dále je v rámci práce řešen výpočet pístní tyče a dna servomotoru. Je provedena studie minimalizace plunžrů servomotoru změnou kinematiky regulace a stanovení minimálního tlaku v tlakovém zásobníku oleje. Práce je řešena pro firmu Litostroj Power, ČKD Blansko Engineering, a.s. V závěru práce jsou uvedeny výsledky a je provedeno jejich zhodnocení.

This thesis is focused on determination of forces acting to regulation ring of water power plant Markersbach (Germany). Solution of the problem is realized for two variants of servomotors – with and without servomotors acting surfaces balancing. Next topics of this thesis are strenght calculation of piston rod and bottom of the servomotors. Minimalization of the size of servomotors plungers by change of regulation kinematics has been done and minimal pressure in the pressure tank is determined. At the conclusion of this thesis received results are mentioned and its interpretation has been done. This thesis is provided for company Litostroj Power, ČKD Blansko Engineering, a.s.
Drive of control ring PVE Merkersbach
Keywords: Servomotor; táhlo servomotoru; regulační kruh; hydraulický okruh; regulace.; Servomotor; piston rod; control ring; hydraulic circle; regulation.